Is Framing More Effective Than Regulating Disclosures? The Effects of Risk Disclosure Frame and Regime on Managers' Disclosure Choices* - Yeo, Feng (Contemporary Accounting Research, 2021)
ABSTRACT I conduct an experiment with senior executives (CEOs, CFOs, controllers) to examine how their risk disclosure quality, with respect to disclosure volume and specificity, is influenced by three factors: first, whether the disclosure behavior is framed internally by the firm as obtaining a gain or avoiding a loss from disclosure; second, whether the external disclosure regime mandates risk mitigation disclosures that explain how a risk is handled; and third, whether the risk under consideration for disclosure is weakly or strongly mitigated. This research question is important because high‐quality risk disclosures are challenging to regulate and changing how disclosure behavior is framed could substitute for costly disclosure regulations. I predict and find that a gain frame prompts managers to make more detailed risk disclosures than a loss frame, regardless of the disclosure regime. I also predict and find that a loss frame leads to less detailed and more boilerplate disclosure of weakly mitigated risks when risk mitigation plans are mandated. Given that the SEC is considering mandating risk mitigation disclosures similar to the practice in other regimes, my findings provide insights on the limitations of mandating these disclosures. My results suggest that changing managers' disclosure frame internally through firm initiatives could be more effective in prompting higher‐quality risk disclosures.